Brine Convection, Temperature Fluctuations, and Permeability in Winter Antarctic Land‐Fast Sea Ice. Issue 1 (12th January 2018) - Wongpan, P.; Hughes, K. G.; Langhorne, P. J.; Smith, I. J.
Abstract: Vertical temperature strings are used in sea ice research to study heat flow, ice growth rate, and ocean‐ice‐atmosphere interaction. We demonstrate the feasibility of using temperature fluctuations as a proxy for fluid movement, a key process for supplying nutrients to Antarctic sea ice algal communities. Four strings were deployed in growing, land‐fast sea ice in McMurdo Sound, Antarctica. By smoothing temperature data with the robust LOESS method, we obtain temperature fluctuations that cannot be explained by insolation or atmospheric heat loss. Statistical distributions of these temperature fluctuations are investigated with sensitivities to the distance from the ice‐ocean interface, average ice temperature, and sea ice structure. Fluctuations are greatest close to the base (<50 mm) at temperatures >−3°C, and are discrete events with an average active period of 43% compared to 11% when the ice is colder (–3°C to −5°C). Assuming fluctuations occur when the Rayleigh number, derived from mushy layer theory, exceeds a critical value of 10 we approximate the harmonic mean permeability of this thick (>1 m) sea ice in terms of distance from the ice‐ocean interface. Near the base, we obtain values in the same range as those measured by others in Arctic spring and summer. The permeability between the ice‐ocean interface and 0.05 ± 0.04 m above it is of order 10 −9 m 2 . Columnar and incorporated platelet ice permeability distributions in the bottom 0.1 m of winter Antarctic sea ice are statistically significantly different although their arithmetic means are indistinguishable. Key Points: Observed temperature fluctuations of ∼ 0.01 ° C and shorter than 12 h are proxies for brine convection in sea ice Temperature fluctuations in thick, growing, Antarctic sea ice occur sporadically near the ice‐ocean interface where temperature is >–3°C Near the ice‐ocean interface, in situ estimates of columnar and incorporated platelet ice permeability overlap, and agree with previous work